2014
DOI: 10.1111/1469-0691.12685
|View full text |Cite
|
Sign up to set email alerts
|

Potential association of specific Candida parapsilosis genotypes, bloodstream infections and colonization of health workers' hands

Abstract: Fungal nosocomial infections continue to be a serious problem among hospitalized patients, decreasing quality of life and adding millions of euros to healthcare costs. The aim of this study was to describe the pattern of fungi associated with the hands of healthcare workers and to genotype Candida parapsilosis isolates in order to understand whether their high clinical prevalence stems from endemic nosocomial genotypes or from the real emergence of epidemiologically-unrelated strains. Approximately 39% (50/129… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 35 publications
2
36
0
2
Order By: Relevance
“…However, more recently some European regions, including southern L. S. Barbedo and others Italy, have reported bloodstream incidences for C. parapsilosis infection of around 60 %, similar to those observed in Brazil (Delfino et al, 2014). Moreover, the distribution of C. orthopsilosis and C. metapsilosis as agents of invasive infections has marked variability.…”
Section: Discussionmentioning
confidence: 58%
“…However, more recently some European regions, including southern L. S. Barbedo and others Italy, have reported bloodstream incidences for C. parapsilosis infection of around 60 %, similar to those observed in Brazil (Delfino et al, 2014). Moreover, the distribution of C. orthopsilosis and C. metapsilosis as agents of invasive infections has marked variability.…”
Section: Discussionmentioning
confidence: 58%
“…This hypothesis is supported by the microbiological tests that confirmed clonal similarity of isolates tested and high rate of fluconazole resistance which is uncharacteristic for this species (<5%) . A possible horizontal yeast transmission by healthcare personnel, as already reported by Delfino et al, could not be excluded. Indeed, outbreaks due to C parapsilosis have been reported, especially in neonatal setting, and in such cases reduced sensitivity and cross‐resistance to triazoles was found .…”
Section: Discussionmentioning
confidence: 99%
“…However, C. parapsilosis complex had a higher isolation rate than C. albicans in the ICU settings of our hospital settings. Delfino et al [25] showed that some C. parapsilosis genotypes recovered from the hands of healthcare workers were also found in blood samples. It could be that the high number of BSIs caused by C. parapsilosis complex might be, at least in part, attributable to the horizontal transmission of this species by hospital staff.…”
Section: Discussionmentioning
confidence: 99%